Short Views on Insect Genomics and Proteomics Insect Proteomics, Vol.2 - Raman, Chandrasekar; Goldsmith, Marian R.; Agunbiade, Tolulope A. (Entomology in Focus,, 2016)
Volume 2 comprises 10 chapters emphasizing proteomics and other "omics" approaches for gaining fundamental knowledge of ticks, malaria mosquitoes, caterpillar larvae, spiders, and other arthropods, and practical applications for the specialized substances they produce. Included are comprehensive reviews of the tick salivary gland proteome, the lepidopteran larval peritrophic matrix, and circadian changes in the malaria mosquito proteome, the biochemistry of insect cold adaptation, and the evolutionary loss of selenocysteine from insect lineages. Surveyed are antimicrobial peptides for medical therapeutics, advanced insect systems for expressing biologically active proteins, properties and uses for spider silks, and novel nano-insecticides from bio-active plant extracts. The editors have assembled top-quality scientists from diverse fields of insect genomics, proteomics and biotechnology to produce a major new work. The chapters of this series (Volumes 1 & 2) present many experts' contributions, providing a concise overview of recent advances by highlighting their current research. The chapters are accessible to wide audience, helping students, postdocs, and researchers to broaden their knowledge and gain an understanding of the challenges and opportunities in each field. Emphasis is on innovative effective and ecologically sound approaches based on the knowledge of insect science to improve public health and agriculture.